Penguatan Kepercyaan Publik Terhdap Unnes Melalui Citizen Journalism - Amin, Syaiful; Kurniawan, Edi; Lusianto, Junaidi Fery (Universitas Negeri Semarang, 2021)
As an agency that has direct contact with the media and public attention, UNNES pays special attention to how to strengthen public trust. Efforts started from internal campus parties to invite relevant partners to support the realization of the effort to produce a reliable and competent journalist. This service aims to educate how important it is to present correct data and balanced news. The method of this activity is online and offline training. This training takes place in 4 stages of training. The participants of this activity are students. Stage 1 takes place online, and stages 2-4 take place offline with a limited number of participants and implementing strict Health protocols. This training activity went smoothly and well. Participants were very enthusiastic during the training activities. Based on the results of the evaluation using a questionnaire and participants as respondents, the training process which includes the preparation of material and the suitability of the answers during the QA process is also considered good.